Perbedaan Rasio Kadar Serum MMP-9/TIMP- 1 pada Kejadian Infark Miokard Akut Elevasi Segmen ST (IMA-EST) dan Sindroma Koroner Akut Non Elevasi Segmen-ST (SKA-NEST) - Basuki Rahmat; Lucia Kris Dinarti; Irmalita I; Budi Yuli Setianto (Jurnal Kardiologi Indonesia, 2013)
Background: Differences between the pathogenesis of ST-Elevation Myocardialinfarction (STEMI) and Non-ST Elevation Acute Coronary Syndrome(NSTE-ACS) had yet unknown. Matrix metalloproteinase-9 (MMP-9) as thematrix degradation enzyme secreted by inflammatory cells play a role in thepathogenesis of plaque rupture. MMP-9 proteolytic activity is inhibited byspecific inhibitors of the Tissue Inhibitor of metalloproteinase-1 (TIMP-1).MMP-9/TIMP-1 ratio describes the actual proteolytic activity of MMP-9.This ratio may distinguish the pathogenesis of STEMI and NSTE-ACS.Objective: To examine the difference serum level ratio MMP-9/TIMP-1 inpatients with STEMI and NSTE-ACS.Methods and subjects: This is a cross-sectional study which recruits patientsconsecutively with ACS admitted to ICCU of Dr. Sardjito General Hospital Yogyakartawithin 24 h onset. Acute infection, chronic inflammation, acute stroke,kidney failure requiring renal replacement therapy, chronic heart failure, liver cirrhosis,acute exacerbation of COPD and pneumonia, thromboembolic disease,malignancy, pregnancy and the use of steroids and steroid anti-inflammatorydrugs are excluded. Serum levels of MMP-9 and TIMP-1 examined using themethod of sandwich enzyme-linked immunosorbent assay (ELISA).Results: The total of 60 subjects with STEMI patients 31 (51.7%) and NSTEACS29 (48.3%). Level of serum MMP-9/TIMP-1 ratio is significantly higher inSTEMI compared to NSTE-ACS (1.106 ± 0.065 vs. 1.046 ± 0.057, p <0.001).MMP-9/TIMP-1 ratio in serum is an independent factor for STEMI (p = 0.003)followed by blood sugar level (p = 0.013) and MMP-9 (p = 0.033). Interestingly,patients with serum MMP-9/TIMP-1 ratio> 1.0639 has a prevalence riskof 1.7 times having STEMI (p = 0.039; KI95% from 1.040 to 8.508). Levels ofserum MMP-9/TIMP-1 ratio significantly higher in STEMI compared to NSTEMIgroup (p = 0.003) and in the STEMI and UAP group (0.026), but did not differsignificantly in NSTEMI and UAP group (p = 0.045).Conclusion: High levels of serum MMP-9/TIMP-1 ratio in patients withSTEMI than NSTEACS may explain the role of serum MMP-9/TIMP-1 ratioin differentiating the pathogenesis of STEMI and NSTE-ACS.(J Kardiol Indones. 2013;34:160-6)